Evaluasi Penggunaan Antibiotik pada Pasien Infeksi Saluran Kemih di Instalasi Rawat Inap RSUP X di Klaten Tahun 2017 - Nawakasari, Nawang; Nugraheni, Ambar Yunita (Pharmacon: Jurnal Farmasi Indonesia, 2019)
Urinary tract infections are infections are characterized by the presence of bacteria that grow and multiply in the urinary tract in excess of the normal amount. Based on the Indonesian Health Profile, urinary tract infections (UTI) are the 10 most common causes of death. Improper use of antibiotics can cause no therapeutic effect and resistance. This study aims to evaluate the accuracy of antibiotic use in patients with urinary tract infections in central hospital Klaten in 2017 covers the right indication, right patient, right medication, and right dosage. Research with non-experimental methods of data retrieval retrospectively and analyzed descriptively. The inclusion criteria in this study were adult patients 18-64 years old, inpatients suffering from urinary tract infections including cystitis and pyelonephritis, receiving antibiotics and complete medical record data. The results showed that patients with urinary tract infections in RSUP in Klaten 2017 had 72 patients with 76 antibiotic prescriptions. Based on the number of patients, the evaluation results showed the right indication is 100% and the right patients is 100%, while the exact evaluation results of the right drug is 96.05% and the right doses is 27,63%.